SCHOOL-BASED TEACHER DEVELOPMENT PROGRAMS IN SECONDARY SCHOOLS IN SRI LANKA - Bandara, Senevirathna (International Journal of Research -GRANTHAALAYAH, 2018)
Teacher professional development is the ‘key’ of the developing students’ quality of the outcomes in the 21st century. Under such a situation, teachers have to update and intensify their knowledge, skills, attitudes and practices according to students’ current expansive demand. In this context, School-Based Teacher Professional Development is a very important concept, because it allows teachers to plan, organise and implement their own professional development programs, considering their particular needs, as well as those of students and school. However, this concept has not been extensively developed in the Sri Lankan education context. Focusing on the Sri Lankan secondary school context, this study examines the possibilities, effectiveness, strategies, issues and challenges involved in implementing these programs in the teachers’ professional development. Simultaneously, the situation of the Non-School-Based Teacher Development programs are also examined because these are currently prominent and this study assumed that both programs need to be integrated in order to provide balanced teacher professional development. The qualitative research approach and the case-study method has been employed. The data were collected by conducting interviews, non-participative observation and sample-based documentary searching. According to the findings, strong recommendations were proposed and relevant guidelines were suggested for future researches.